Single crystalline Ge thin film growth on c-plane sapphire substrates by molecular beam epitaxy (MBE). Issue 24 (31st May 2022) - Wangila, Emmanuel; Saha, Samir K.; Kumar, Rahul; Kuchuk, Andrian; Gunder, Calbi; Amoah, Sylvester; Khiangte, Krista R.; Chen, Zhong; Yu, Shui-Qing; Salamo, Gregory J.
Abstract : Molecular beam epitaxy (MBE) was used to grow dissimilar materials like cubic Ge on a hexagonal c -plane sapphire substrate. To the authors' best knowledge, this is the first time single crystalline Ge was grown on a c -plane sapphire substrate. Abstract : Single crystalline Ge has been grown on c -plane sapphire substrates by molecular beam epitaxy. Direct growth of Ge on sapphire results in three-dimensional (3D) Ge islands, two growth directions, more than one primary domain, and twinned crystals. The introduction of a thin AlAs nucleation layer significantly improved the surface and material quality, which is evident from a smoother surface, single epitaxial orientation, sharper rocking curve, and a single domain. The AlAs nucleation layer thickness was also investigated, and a 10 nm AlAs layer resulted in the lowest surface roughness of 3.9 nm. We have been able to achieve a single primary domain and reduced twinning relative to previous works. A high-quality Ge buffer on sapphire has the potential as an effective platform for the subsequent growth of GeSn and SiGeSn for microwave photonics.